GUIDED INQUIRY AND GUIDED DISCOVERY MODEL IN SCIENCE LEARNING TO ‎IMPROVE COGNITIVE ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - syafrilianto syafrilianto syafrilianto; taufik rahman (EDUSAINS, 2017)
This study aims to find out the improvement of cognitive ability through the implementation of guided inquiry and guided discovery model in integrated natural science learning. Alternative energy sources was chosen as the learning theme which contain Biology, Physic, Chemistry concepts, which consist of briquettes as the heat source, and battery as the power source. This study used quasi experiment method with matching only pretest posttest control group design. The subject of this study were 42 students of VII grade of Junior High School in Kampar District which consist of experiment and control class with 21 students in each class. Student cognitive learning outcomes was measured by multiple choice test instrument, which contain of 21 items which was done twice (pretest and posttest). The technic of data analysis was normality test and hypothesis test (U test). Data were analyzed by IBM SPSS 22 statistics and Microsoft Excel 2010 program. The N-Gain average of cognitive ability shows that there is an improvement of student cognitive ability in experiment class as 0,44 with intermediate category, and in control class as 0,21 with low category. While, the result of U test toward N-Gain value shows that there is a significant difference on student cognitive ability between students in experiment and control class. Thus, it can be concluded that guided inquiry model can improve student cognitive ability more than guided discovery model. Keywords: guided inquiry model, discovery guided model, cognitive ability, alternative energy sources